Exploring caesarean delivery in the second stage of labour at a tertiary care hospital: a retrospective study - Jadav, Pravinkumar A.; Dabhi, Palak M.; Rathod, Dhruti A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Caesarean section (CS) performed in the second stage of labour has many implications for maternal and neonatal morbidity as well as for subsequent pregnancies. The objectives of this study were to determine the rates of CS at full dilatation, their indications, associated maternal and neonatal complications. Methods: This retrospective study assessed all the women with a singleton fetus in cephalic presentation at term (≥37 weeks) who underwent CS in the second stage of labor between 1 August 2019 and 31 March 2020 at a tertiary care hospital. Maternal demographics, labour and delivery details as well as neonatal outcomes were collected. Results: During the study period, 2124 (36%) babies were born by CS. Of these, 49 (2.3%) were performed in the second stage of labour at ≥37 weeks of gestation. The most common indication of CS was non-descent of head in 38 (77.55%) of cases. The majority of women 38 (77.55%) delivered by CS in the second stage of labor were primiparous. The 27 (55.10%) women were in the age group of 20-25 years. Most common intraoperative complication was blood-stained urine in 20 (40.81%) women. Overall transfusion rate was 18.36%. Maximum number of babies born 44 (89.79%) were having birth weight between 2.5-3.5 kg. Out of 65 babies born, 17 (34.69%) were admitted to neonatal intensive care unit. Conclusions: Formulation of an institutional protocol and training and supervision of trainees to improve the skill of operative vaginal delivery and second stage cesarean is needed.